Income Inequality and Government Transfers in Mexico - Lambert, Frederic; Park, Hyunmin (Washington, D.C. : International Monetary Fund, 2019)
We analyze microdata from Mexico's survey on household income and expenditures (ENIGH) to study the evolution of income inequality in Mexico over 2004-16, identify its sources, and investigate how it was affected by government social policy. We find evidence of only a small decline in inequality over this period. The observed decline may be attributed to government transfers, notably targeted cash transfers (Prospera) and non-contributory pensions. In 2016, those two programs accounted for more than two thirds of the reduction in the Gini coefficient due to government transfers. Other transfer programs such as farmland subsidies (Proagro), government scholarships, and non-monetary transfers for medical expenditures have not been as effective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet